2017
DOI: 10.1002/ptr.5818
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Toxicological Study ofMaytenus ilicifoliaLeaf Extract. Part I - Preclinical Studies

Abstract: One of the Brazilians medicinal plants most cited in ethnopharmacological surveys for the treatment of ulcers and gastric diseases was evaluated for its efficacy and toxicity. Maytenus ilicifolia leaf extract (MIE) was acutely and chronically (180 days) administered to rats, mice, and dogs. Acute tests were antiulcer effect and toxicological trials (observational pharmacological screening, LD50, motor coordination, sleeping time and motor activity). Chronic tests were the following: weight gain/loss and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…Among its pharmacological activities, anti-ulcerogenic activity stands out, which can be compared to the action of ranitidine and cimetidine. 45 Tabach et al demonstrated in important preclinical 46 and clinical 47 studies the toxicological safety and therapeutic efficacy in humans following the use of standardized M. ilicifolia extract. H 2 receptor antagonists like ranitidine, cimetidine, reversibly, and competitively inhibit histamine binding while proton pump inhibitors like omeprazole and pantoprazole by inhibiting gastric acid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Among its pharmacological activities, anti-ulcerogenic activity stands out, which can be compared to the action of ranitidine and cimetidine. 45 Tabach et al demonstrated in important preclinical 46 and clinical 47 studies the toxicological safety and therapeutic efficacy in humans following the use of standardized M. ilicifolia extract. H 2 receptor antagonists like ranitidine, cimetidine, reversibly, and competitively inhibit histamine binding while proton pump inhibitors like omeprazole and pantoprazole by inhibiting gastric acid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Em ambos os estudos, segundo os autores, foram constatadas propriedades curativas cicatrizantes das úlceras gástricas e antimicrobianas para o controle da Helicobacter pylori. Estudos mais recentes corroboram a ação da espinheira santa na redução de problemas gástricos (PÉRICO et al, 2018;TABACH et al, 2017). Pessuto et al (2009) identificaram em folhas de M. ilicifolia a presença de procianidina B 1 (epicatequina-(4β→8)-catequina) e procianidina B 2 (epicatequina-(4β→8)epicatequina).…”
Section: Composição Fitoquímica Da Espinheira-santaunclassified
“…Os pacientes foram acompanhados em relação ao perfil bioquímico, funções psicomotoras e reações adversas. Os resultados demostram que mesmo em altas dosagens o extrato é bem tolerado, com poucas mudanças no perfil bioquímico, hematológico, função psicomotora e sem reações adversas significantes(TABACH et al, 2017)…”
unclassified